The Effect Of Perceived Organizational Support On Organizational Citizenship Behavior With Work Engagement As A Mediation Variable - Sakarina, Sari; Haekal, T. M; Pratiwi, Ratih; Cakranegara, Pandu Adi; Rusliandy, Rusliandy; Kasuma, Jati (Jurnal Manajemen Industri dan Logistik, 2022)
The purpose of this study was to determine the effect of Perceived Organizational Support on Organizational Citizenship Behavior with the work engagement variable as a mediator at the Palembang City Tourism Office. Samples were taken as many as 63 employees. Data was collected by distributing questionnaires using a 5-point Likert scale to measure 22 statement items. The analysis technique used is Path Analysis. The results of the analysis show that Perceived Organizational Support has a positive and significant effect on organizational citizenship behavior, Perceived Organizational Support. This study also succeeded in proving that Perceived Organizational Support has an effect on Organizational Citizenship Behavior mediated by Work Engagement at the Palembang City Tourism Office. Based on the results of research analysis, several suggestions can be used as consideration in determining future policies, namely, the Office should pay more attention to any complaints felt by employees so that it will create a sense of meaning and feelings of pleasure and employees feel considered necessary by the service.